Low treatment completion rates reveal gaps in the LTBI care cascade among university students - Murthy, Anu K.; Goodman, Richard A.; Moore, Miranda A. (Frontiers in Tuberculosis, 2025)
BackgroundUniversity students, particularly those from tuberculosis (TB)-endemic countries and students in health professions, are at increased risk for latent tuberculosis infection (LTBI). In the United States (U.S.), TB screening is required for applicants for permanent residency and refugee status but not for individuals entering on student visas, and institutional policies vary. At our university, which requires pre-matriculation TB screening for all incoming students, low LTBI treatment completion rates prompted a review of care delivery.MethodsWe conducted a retrospective chart review of students diagnosed with LTBI at a medium-sized private university from 2018 to 2023. Records identified by ICD-10 codes were reviewed for demographics, school enrollment, testing method, regimen, and treatment outcome.ResultsOf 687 students with TB-related visits, 82 (12%) were diagnosed with LTBI. Median age was 27 years (interquartile range 23–31); 55% were female and 65% were non-U.S.-born, most often from China and India. Students represented nine schools, with Medicine (17%) and Nursing (14%) comprising about one-third of cases. Forty-eight students (59%) initiated treatment, while 34 (41%) did not, primarily due to declining therapy or incomplete follow-up. Among those treated, 22 (46%) completed therapy, corresponding to 27% overall. Completion was highest for nine months of isoniazid (88%) and lowest for 4 months of rifampin (17%). Several documentation and follow-up gaps were identified.ConclusionLosses across the LTBI care cascade were common in this university setting and reflect patterns reported in other U.S. and international studies. Strengthening education, follow-up, access to shorter regimens, and documentation may improve completion rates and support TB elimination goals.